2018
DOI: 10.1680/jmacr.17.00042
|View full text |Cite
|
Sign up to set email alerts
|

Numerical modelling of plastic–damage response and crack propagation in RAC under uniaxial loading

Abstract: In order to better understand the failure mechanism of recycled aggregate concrete (RAC), a numerical study on modelled recycled aggregate concrete (MRAC) was conducted to investigate the plastic–damage response and crack propagation under uniaxial loading. In the numerical model, the nanoscale mechanical properties and the thickness of the interfacial transition zones (ITZs) were obtained based on advanced nanoindentation. The constitutive relationships of new and old cement mortars and corresponding ITZs wer… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
16
0

Year Published

2018
2018
2023
2023

Publication Types

Select...
3
2

Relationship

1
4

Authors

Journals

citations
Cited by 32 publications
(16 citation statements)
references
References 37 publications
0
16
0
Order By: Relevance
“…Compared with experimental methods, numerical simulation seems more convenient and low‐cost, although the accuracy is sacrificed through idealizing the real self‐healing behavior and the complex properties of cementitious materials . Nevertheless, numerical analysis is a valuable technique to investigate self‐healing mechanics with parametric analysis, if there are improvements in assumptions of the nonuniform and multiaxial load conditions and consideration of the inconsistency between the capsules and cement matrix .…”
Section: Encapsulation‐based Self‐healing Concretementioning
confidence: 99%
“…Compared with experimental methods, numerical simulation seems more convenient and low‐cost, although the accuracy is sacrificed through idealizing the real self‐healing behavior and the complex properties of cementitious materials . Nevertheless, numerical analysis is a valuable technique to investigate self‐healing mechanics with parametric analysis, if there are improvements in assumptions of the nonuniform and multiaxial load conditions and consideration of the inconsistency between the capsules and cement matrix .…”
Section: Encapsulation‐based Self‐healing Concretementioning
confidence: 99%
“…It is commonly found that the structure and characteristics of RAC are different from natural aggregate concrete (NAC) . Compared with NAC at the mesoscale, the structure of RAC is much more sophisticated, and the primary ingredients of an RAC model are regarded as a five‐phase system .…”
Section: Introductionmentioning
confidence: 99%
“…To save the resources, energy, time, and costs associated with experimental testing when conducting scientific research, [1][2][3][4] numerical investigations have become an extremely effective discipline for studying the mechanical properties of materials [5][6][7][8] and structures 2,9 and have therefore been widely used by many researchers. 6,[10][11][12][13][14] The finite element method (FEM) was first proposed by Clough.…”
Section: Introductionmentioning
confidence: 99%
See 2 more Smart Citations